Access to confidential information in the financial and banking sectors: judgements of the Court of Justice in Altmann, Baumeister, UBS and Buccioni. Issue 4 (2nd October 2019) - Farinhas, Carla
Abstract : In the years between 2014 and 2018, in judgements Altmann, Baumeister, UBS and Buccioni, the Court examined the scope of the obligation of professional secrecy incumbent on financial and banking supervisory authorities of Member States pursuant to Article 54 MiFID and Article 53 CRD. The Court has not only clarified the notion of "confidential information" but has also provided guidance to national courts on how to reconcile the concerns which underpin the obligation of professional secrecy laid down by the EU legislator in this field and certain core values to democracy and to the rule of law in the EU.